Working memory, attention and their relationship: A theoretical overview (Research, Society and Development, 2021)
It is broadly agreed that working memory and attention constitute two significant cognitive skills that are closely related. Their relationship has been proved to be intertwined and has attracted intense research interest. It is worth noting that, due to the growth of cognitive neuroscience and neuroimaging studies, there have been many fruitful steps towards further interpreting this link between working memory and attention. In this article, there has been an attempt to explore the concept of working memory and attention and delineate several theoretical options for conceptualizing their relationship. Furthermore, in this article, many neuroscientific aspects of working memory, attention, and their relationship are presented to inform the readers about these concepts and motivate them to deepen their understanding of working memory and attention. Simultaneously, the present article highlights the importance of working memory, attention, and their relationship for the individuals’ proper cognitive function and, generally, their function and attitude in daily life.